Targeting tumor-associated genes, immune response, and circulating tumor cells in intrahepatic cholangiocarcinoma: Therapeutic potential of Atractylodes lancea (Thunb.) DC - Martviset, Pongsakorn; Chantree, Pathanin; Tongsiri, Nisit; Plengsuriyakarn, Tullayakorn; Na-Bangchang, Kesara (PloS one, 2025)
Cholangiocarcinoma (CCA) is one of the most aggressive cancers with a poor prognosis. Current treatment strategies involve hepatobiliary surgery, chemotherapy, radiotherapy, and supportive care; however, the success of these treatments remains limited. Therefore, this study investigated the potential of Atractylodes lancea (Thunb) D.C. (AL) in limiting the progress of CCA by targeting the expression of cancer-related genes involved in immune responses and circulating tumor cells. The study was part of Phase 2A clinical trial in advanced-stage intrahepatic iCCA (iCCA) patients: Group 1 (n = 16) received low-dose AL (capsule formulation of the standardized extract of AL: CMC-AL) with standard supportive care, Group 2 (n = 16) received high-dose AL with standard supportive care, and Group 3 (n = 16) received standard supportive care alone. Venous whole blood samples (EDTA, 5 ml) were collected from each patient on Day 1 and Day 90 and the non-CCA subjects (n = 16) on Day 1. Fifty-nine samples (48 and 11 samples for Day 1 and Day 90, respectively) were processed for total RNA isolation. Gene expression was evaluated using reverse transcription followed by a PCR array. Regardless of dosage, gene expression patterns in the AL-treated groups closely resembled those of the healthy subjects. Specifically, cancer-associated genes, including VEGF-A , NR4A3 , Ki-67 , and EpCAM , were significantly down-regulated. Additionally, the expression levels of immune-related genes were modulated in AL-treated patients. The treatment groups exhibited lower levels of the pro-inflammatory cytokine IL-6 , increased expression of the anti-inflammatory cytokine IL-10, and cell-mediated immune-related molecules such as CTLA4 and PFR1 . These findings suggest the potential of AL for iCCA treatment. However, additional studies are required to confirm the correlation between gene and protein expression profiles, as well as CTCs profile.